Case Report: Area of focus - involuntary admission for severe Factitious Disorder imposed on self - Eng, Sim Leng; Neo, Hui Ling Michelle; Chang, Cheryl Wai Leng (Frontiers in Psychiatry, 2025)
Factitious Disorder is clinically challenging to diagnose owing to its reliance on unequivocal evidence of deception. The nature of the disorder and lack of definitive treatment may limit utilisation of mental health legislation, despite its potential fatality. Here, we report a case of a young lady with recurrent, unexplained and life-threatening episodes of iron-deficiency anaemia. Lack of reliable informant to clarify suspicion of Factitious Disorder as well as overshadowing of legal and ethical dilemmas further complicate the clinical management. An involuntary admission, as a last resort, had assisted to solidify the diagnosis of factitious disorder and enforced necessary therapeutic interventions. This Case Report is the first report to highlight the exceptional use of involuntary admission involving a patient with life-threatening factitious anaemia, in Singapore context. It sets the precedence for the exceptional application of the MHCTA outside of gazetted institutions in Singapore, in context of probable severe factitious anaemia.